Data processing correction of the irising effect of a fast-gating intensified charge-coupled device on laser-pulse-excited luminescence spectra - Ondic, L; Dohnalová, K; Pelant, I; Zídek, K; de Boer, W D A M (The Review of scientific instruments, 2010)
Intensified charge-coupled devices (ICCDs) comprise the advantages of both fast gating detectors and spectrally broad CCDs into one device that enables temporally and spectrally resolved measurements with a few nanosecond resolution. Gating of the measured signal occurs in the image intensifier tube, where a high voltage is applied between the detector photocathode and a microchannel plate electron multiplier. An issue arises in time-resolved luminescence spectroscopy when signal onset characterization is required. In this case, the transient gate closing process that causes the detected signal always arises in the middle of the ICCD chip regardless of the spectral detection window--the so-called irising effect. We demonstrate that in case when the detection gate width is comparable to the opening/closing time and the gate is pretriggered with respect to the signal onset, the irising effect causes the obtained data to be strongly distorted. At the same time, we propose a software procedure that leads to the spectral correction of the irising effect and demonstrate its validity on the distorted data.